2018
DOI: 10.1186/s13620-018-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-milking teat disinfection on new mastitis infection rates of dairy cows

Abstract: BackgroundThe practise of teat disinfection prior to cluster attachment for milking is being adopted by farmers in Ireland, particularly where there are herd issues with new infection rates. Pre-milking teat disinfection has been shown to reduce bacterial numbers on teat skin and to be most effective against environmental bacteria such as Escherichia coli and Streptococcus uberis. A split udder design experiment was undertaken on two research herds (A = 96 cows: B = 168 cows) to test the benefit of pre-milking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 23 publications
5
36
0
3
Order By: Relevance
“…High bacterial contamination may increase the chances of more bacteria entering the teat orifice and causing infection [1]. The removal of bacteria pre- and post-milking can lower the occurrence of new intramammary infections (IMI’s) [2, 3]. Therefore, determining the efficacy of teat disinfectant products against bacteria naturally present on teat skin is important.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High bacterial contamination may increase the chances of more bacteria entering the teat orifice and causing infection [1]. The removal of bacteria pre- and post-milking can lower the occurrence of new intramammary infections (IMI’s) [2, 3]. Therefore, determining the efficacy of teat disinfectant products against bacteria naturally present on teat skin is important.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, determining the efficacy of teat disinfectant products against bacteria naturally present on teat skin is important. Teat swabbing has been used to determine the effect of pre-milking teat preparation treatments [1, 2, 46], enumerate and identify bacteria present on teat skin surface [7–11]. Previous studies focused on evaluating pre-milking teat cleaning procedures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barkema et al (1998) and Kelly et al (2009) reported that washing with a towel before teat dipping was one of the important factors related to the low number of Somatic Cell Count (SCC). Supar and Ariyanti (2008) added that the transmission process of (Gleeson et al, 2018). Teat dipping after milking is primarily given to infected groups and has been shown to be very effective in preventing the spread of mastitis (Galton, 2004).…”
Section: Milking Managementmentioning
confidence: 99%
“…Teat disinfection that effectively and safely reduces bacterial load on teat skin reduces the risk of mastitis in the herd (17)(18)(19), improves teat skin condition (9), and reduces the risk of milk contamination (20). The observed efficacy of a teat disinfectant will vary depending on the production system, season, and the particular mastitis causing pathogens affecting the herd (18,21,22).…”
Section: Introductionmentioning
confidence: 99%